2000
DOI: 10.1002/1097-4636(20000905)51:3<391::aid-jbm13>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced guided bone regeneration by controlled tetracycline release from poly(L-lactide) barrier membranes

Abstract: With the aim of providing effective periodontal therapeutic modality, drug-releasing membranes for guided tissue regeneration (GTR) were developed. As GTR membranes, biodegradable barrier membranes composed of porous poly(L-lactide) (PLLA) films cast on poly(glycolide) (PGA) meshes were fabricated using an in-air drying phase inversion technique. PLLA was dissolved in methylene chloride-ethylacetate mixtures, cast on knitted PGA mesh, and then air-dried. Tetracycline, which is used in periodontal therapy becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 20 publications
2
45
0
1
Order By: Relevance
“…In this study, genipin-crosslinked electrospun chitosan was able to absorb minocycline and release it in an extended manner that remained bacteriostatic for longer periods than uncrosslinked membranes (8 days as compared to 4 days). These results are similar to reports by others who have loaded biodegradable GTR membranes with antibiotics/antiseptics such as tetracycline, doxycycline or chlorhexidine [15][16][17]. Delayed degradation kinetics (Norowski et al, in review) contributed to the extended release seen from crosslinked membranes.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, genipin-crosslinked electrospun chitosan was able to absorb minocycline and release it in an extended manner that remained bacteriostatic for longer periods than uncrosslinked membranes (8 days as compared to 4 days). These results are similar to reports by others who have loaded biodegradable GTR membranes with antibiotics/antiseptics such as tetracycline, doxycycline or chlorhexidine [15][16][17]. Delayed degradation kinetics (Norowski et al, in review) contributed to the extended release seen from crosslinked membranes.…”
Section: Discussionsupporting
confidence: 89%
“…It is recognized that the bone regeneration in periodontal defects has increased by local administration of tetracycline due to its anticollagenolytic effect, which enhances bone forming ability via osteoblast cell chemotaxis and hence reducing bone resorption. Also it promotes the growth of alveolar bone in periodontal therapy [24]. Therefore controlled delivery of tetracycline from the polymer-grafted HA may be highly beneficial for the treatment of infectious bone diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Barrier membranes for guided tissue regeneration (GTR) are based on the concept of physical separation between the tissue compartment and bone defect sites. [1] Barrier membranes must satisfy space maintenance, tissue integration, cell-occlusiveness, and biocompatibility criteria. Of these properties, optimal space maintenance is the most important property to ensure the success of the periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported that some periodontal pathogens could colonize and adhere to the GTR membrane. [1] Tetracycline is a well-known antibiotic that is effective against many periodontal diseaserelated microorganisms. [6] Many researchers have studied biodegradable membranes such as collagen and a synthetic biodegradable polymer for use in GTR.…”
Section: Introductionmentioning
confidence: 99%